"Bookmysurprise": navigating through the predicament of a start-up. Issue 2 (16th August 2021) - Bansal, Shagun; Kapur, Inakshi; Singh, Anjani Kumar; Verma, Piyush
Abstract : Learning outcomes: The learning outcomes of this paper are as follows: to identify the pros and cons of waged employment and entrepreneurship, to identify the contextual factors influencing entrepreneurship, to set up a new venture, namely, steps, challenges involved and decision-making process, to scale up a small business; when, how and where? And to tradeoff required for scaling up a small business. Case overview/synopsis: Pooja, a young management graduate from Varanasi, decided to overcome all challenges and barriers faced by a women entrepreneur and chase her lifelong dream of creating her own event management startup. After having achieved phenomenal success in a short period of time within the city, she began to receive interest from neighbouring cities as well. The decision to scale up operations was particularly difficult for Pooja, as she had funded the venture through her personal funds and personally nurtured the business and her team based on the values of quality and creativity. Like any small business, she had to decide what level of trade-off was required between scaling and dilution of control over the operations. Complexity academic level: The case study is applicable for students of management. The learnings from the case can be applied by an individual who is looking to start a business or expand one. Supplementary materials: Teaching Notes are available for educators only. Subject code: CSS 3: Entrepreneurship.